IMPACT OF AGE IN HEALTH-RELATED QUALITY OF LIFE IN OLDER ADULTS WITH CANCER - Coeli Regina Carneiro Ximenes; Anke Bergmann; Jurema Telles de Oliveira Lima; Arlene Santos Cavalcanti; Murilo Carlos Amorim de Britto; Maria Julia Gonçalves Mello; Luiz Claudio Santos Thuler (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To evaluate the impact of age in health-related quality of life (HRQoL) in older adults with cancer. METHODS: This was a cross-sectional study of 608 older adults diagnosed with cancer. Age groups were considered an independent variable. For the analysis of HRQoL, the mean scores of age groups were compared by analysis of variance and the Scheffé comparison test. For measuring the association between age and HRQoL, we used simple and multiple linear regression analyses. RESULTS: Cognitive function showed the highest scores (average 87.94 ± 26.87), while physical function showed the lowest ones (68.04 ± 28.63). The highest symptom score was observed for financial difficulties (34.21 ± 39.06), followed by pain (29.47 ± 33.92) and insomnia (28.51 ± 37.03). After adjustment, we observed a decrease in physical function (p = 0.028) and an improvement in emotional function (p = 0.003) with increasing age. CONCLUSIONS: In older patients with cancer, age negatively impacted physical function and positively impacted emotional function.